Measurement of the B-s(0) -> J/psi K-S(0) branching fraction - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (2012)
The B s0→J/ψK S0 branching fraction is measured in a data sample corresponding to 0.41fb -1 of integrated luminosity collected with the LHCb detector at the LHC. This channel is sensitive to the penguin contributions affecting the sin2β measurement from B 0→J/ψK S0. The time-integrated branching fraction is measured to be B(B S0→J/ψK S0)=(1.83±0.28)×10 -5. This is the most precise measurement to date. © 2012 CERN.